The pragmatic strategies in selected Malaysia formal letters : a study of politeness,presuppositon and implicature - Myra Aidrin binti Mohd Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study was carried out to see how pragmatic ambiguity is handled by the English non-native writer of formal letters by analysing the pragmatic strategies of politeness, implicature, and presupposition in the propositions of the letters realised through speech acts, simultaneously looking at how strongly, in terms of quantity and quality, they are manifested in the selected written communication. This study was to prove that pragmatics processes are manifested just as strongly in the most restricted and formal form of written communication despite its basic notion being conversation. This study which is situated in the larger framework of discourse analysis analysed 100 written documents from three different institutions of higher learning, which are dated from 2004 to 2007. Letters are written by Malaysians to Malaysians in English. They are written by and sent to both academic and non-academic staff. These letters may come in paper or electronic forms (e.g., the e-mail). The pragmatic components were analysed by looking at the frequency of occurrences. The results indicated that the amalgamation of politeness, presupposition and implicature are strongly manifested in letters that are dyadic and restricted in nature. These pragmatic strategies are handled by the writers through their linguistic choices that are centered towards politeness dictated by distance, familiarity, and intention of the addresser/ addressee of the letters. Some linguistic choices that determine politeness are seen to be typified in certain situations or actions as they are taken as accepted social rules. Though the linguistic choices are centred towards politeness, the presupposition triggers and implicatures show that the 'what' is somehow more critical in letters than the 'how' to suit with the nature of letters in being economical. Thus pragmatic considerations are just as abundant in writing as they are in spoken. Readers, just like hearers, would still have to make inferences of the writer's intention, to maximise their understanding of all the intended messages in the letter, be they direct or indirect.